2020
DOI: 10.22541/au.159103619.94137268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long term oral and dental effects in adolescents who were treated for cancer in childhood

Abstract: Background: Survival following childhood cancer has increased considerably. We examined associations of specific types of cancer therapy with the presence of oral and dental abnormalities among childhood cancer survivors. Procedure: 131 children who were diagnosed with malignancies during childhood were referred to full oro-dental exams. Permanent teeth were examined clinically and radiographically to identify dental caries and anomalies in dental developmental: hypocalcification or hypoplasia, microdontia, ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 35 publications
(72 reference statements)
1
4
0
Order By: Relevance
“…Owosho et al (2016), and Seremidi et al (2019) in their systematic review also reported microdontia to be the most frequent alteration. These results coincide with ours, but other studies found that the most common dental sequelae were root changes followed by microdontia (Çetiner et al, 2019; Halperson et al, 2020; Kang et al, 2018; Seremidi et al, 2021). The calcification of the first premolars begins between the ages of 1.5 and 2 years, and that of the second premolars and second molars between 2 and 2.5 years and 2–2.5 and 3 years, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Owosho et al (2016), and Seremidi et al (2019) in their systematic review also reported microdontia to be the most frequent alteration. These results coincide with ours, but other studies found that the most common dental sequelae were root changes followed by microdontia (Çetiner et al, 2019; Halperson et al, 2020; Kang et al, 2018; Seremidi et al, 2021). The calcification of the first premolars begins between the ages of 1.5 and 2 years, and that of the second premolars and second molars between 2 and 2.5 years and 2–2.5 and 3 years, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the patients in our sample (85.3%) presented at least one dental sequela as a result of the cancer therapy received, a rate similar to those recorded in other studies (Kang et al, 2018; Kılınç et al, 2019; Nishimura et al, 2013; Owosho et al, 2016; Proc et al, 2016). However, there was a wide variation in the frequency of dental alterations, and other studies have reported much lower percentages (Elzembely et al, 2019; Halperson et al, 2020; Proc et al, 2016). These differences in the frequency of dental alterations can be attributed to the age at which treatment was started, the stage of dental maturity at the time of the clinical examination, the type of cancer therapy administered, and the radiation received, especially in the head and neck region, and the methodological diversity of the studies.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations